Biopsychosocial model of schizophrenia and early maladaptive schemas Part 2. Early maladaptive schemas in patients with schizophrenia - A. P. Kotsubinsky; A. N. Erichev; V. O. Klaiman; O. D. Shmonina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
This article studies the role of early maladaptive schemas in the formation and maintenance of symptoms in patients with schizophrenia. Schemes are supposed to be additional risk factor reducing patients’ adaptive potential and contributing to the exacerbation or recurrence of the disease. Therefore schemas are an important target for psychotherapeutic work with this group of patients. Also in this article we describe the results of study of early maladaptive schemas in patients with schizophrenia spectrum, conducted on the basis of Bekhterev Institute. The findings are compared with the results of other researchers. The idea of the schemas that are typical for this group of patients will contribute to the development of more effective psychotherapeutic methods of rehabilitation and prevention for patients with schizophrenia spectrum disorders.